Nomenclatural and taxonomic study in species of Viola (Violaceae) from Argentina - Nicola, Marcela Viviana; Salomón, Luciana; Zuloaga, Fernando Omar (Phytotaxa, 2018)
During the revision of Viola for the Flora of Argentina project we detected names which need an exhaustive nomenclatural and taxonomic study. As a result of our analysis 43 lectotypes and three neotypes are designated for accepted names and synonyms of the genus as currently recognised by the present authors. Moreover, we encountered a nomen nudum, and present here a new combination and five new synonyms.